The Influence of Education and Economic Growth on Income Inequality in Indonesia - Syintia KHAIRUNNISA; Ditra HARYANI; Rani GUSMIATI; Aulia Dwi Riani PUTRI; Jolianis JOLANIS (International Journal of Environmental, Sustainability, and Social Science, 2025)
The purpose of this study is to examine and analyze the influence of education and economic growth on income inequality in Indonesia partially and simultaneously. The type of research is associative with the object of research being Indonesia. The type of research data is time series data for the period 1961 - 2023, collected from the World Bank. Data collection techniques are carried out using documentation techniques. The dependent variable is income inequality, namely income inequality refers to differences in income received by individuals or groups in a society, where some groups may have much higher incomes than others. The first independent variable is education, namely the level of education measured in percent. The second variable is economic growth, namely the level of economic growth measured in percent. The data analysis technique uses multiple regression.